Answer:
![\left[\begin{array}{c}-\frac{8}{\sqrt{117} } \\\frac{7}{\sqrt{117} }\\\frac{2}{\sqrt{117} }\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bc%7D-%5Cfrac%7B8%7D%7B%5Csqrt%7B117%7D%20%7D%20%5C%5C%5Cfrac%7B7%7D%7B%5Csqrt%7B117%7D%20%7D%5C%5C%5Cfrac%7B2%7D%7B%5Csqrt%7B117%7D%20%7D%5Cend%7Barray%7D%5Cright%5D)
Step-by-step explanation:
We are required to find a unit vector in the direction of:
![\left[\begin{array}{c}-8\\7\\2\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bc%7D-8%5C%5C7%5C%5C2%5Cend%7Barray%7D%5Cright%5D)
Unit Vector, ![\hat{a}=\dfrac{\overrightarrow{a}}{|\overrightarrow{a}|}](https://tex.z-dn.net/?f=%5Chat%7Ba%7D%3D%5Cdfrac%7B%5Coverrightarrow%7Ba%7D%7D%7B%7C%5Coverrightarrow%7Ba%7D%7C%7D)
The Modulus of
=![\sqrt{(-8)^2+7^2+(-2)^2}=\sqrt{117}](https://tex.z-dn.net/?f=%5Csqrt%7B%28-8%29%5E2%2B7%5E2%2B%28-2%29%5E2%7D%3D%5Csqrt%7B117%7D)
Therefore, the unit vector of the matrix is given as:
![\left[\begin{array}{c}-\frac{8}{\sqrt{117} } \\\frac{7}{\sqrt{117} }\\\frac{2}{\sqrt{117} }\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bc%7D-%5Cfrac%7B8%7D%7B%5Csqrt%7B117%7D%20%7D%20%5C%5C%5Cfrac%7B7%7D%7B%5Csqrt%7B117%7D%20%7D%5C%5C%5Cfrac%7B2%7D%7B%5Csqrt%7B117%7D%20%7D%5Cend%7Barray%7D%5Cright%5D)
Answer:
slope is 1
Step-by-step explanation:
5-3/-4--6 = 2/2 = 1
Answer:
2.794
Step-by-step explanation:
Recall that if G(x,y) is a parametrization of the surface S and F and G are smooth enough then
F can be written as
F(x,y,z) = (xy, yz, zx)
and S has a straightforward parametrization as
with 0≤ x≤1 and 0≤ y≤1
So
we also have
and so
we just have then to compute a double integral of a polynomial on the unit square 0≤ x≤1 and 0≤ y≤1
=1/3+2-2/9-2/5+3/2-1/4-1/6 = 2.794
Answer:
The product is 25
Step-by-step explanation:
we know that
The complex number z1 is equal to
z1=(-4-3i)
we know that
To find the complex conjugate of (-4 - 3i) we change the sign of the imaginary part
so
The conjugate is equal to (-4+3i)
therefore
![(-4-3i)(-4+3i)=16-9(-1)=25](https://tex.z-dn.net/?f=%28-4-3i%29%28-4%2B3i%29%3D16-9%28-1%29%3D25)
When you multiply exponents with the same base, you add the exponents.
3+-5+y=-2
-2+y=-2
y=0
Final answer: y=0